The Learning Organization and its Impact on the Development of Organizational Prowess in Private Hospitals in the City of Irbid - AL-Zu”bi, Ghassan Khaled; al-zoubi , Ali Falah (Journal of Ecohumanism, 2024)
The study aimed to identify the learning organization and its impact on the development of organizational prowess in private hospitals in the city of Irbid. The Researchers adopted a quantitative approach that relies on studying the phenomenon as it is, describing it accurately, and then analyzing the correlations. The study community consisted of (250) employees in private hospitals operating in the city of Irbid. The researchers drew a random stratified sample of (105) individuals and he adopted the questionnaire as a tool for the study. The results showed that there is a statistically significant role at the level of significance of learning organization and its impact on organizational prowess and showed that there is a statistically significant role for the dimensions (network organization and administrative empowerment) on organizational prowess in private hospitals in Irbid. The results of the study indicated that the organization's learning dimensions in private hospitals in Irbid came at a high level of evaluation, thus recommended the following: The need to support the efforts of Jordanian private hospitals to adopt the best practices in the field of organizational, exploratory and exploitative prowess, and to benefit from successful experiences in the world in a way that contributes to the development and strengthening of the learning organization, The need to support the efforts of Jordanian private hospitals to adopt the best practices existing in the field of organization prowess, exploration and exploitation, and to build on successful experiences in the world, thereby contributing to the development and strengthening of the educating organization; and the need to work on providing the necessary requirements to facilitate the process of personal excellence such as developing a supportive organizational culture , adopting a clear vision, encouraging innovation and creativity processes and the need to work to strengthen the organizational structures by the surveyed hospitals by moving and transforming from the traditional structure to a flexible and differentiated structure